2015
DOI: 10.1309/lm9owrf64ogqodea
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Autoimmune Hemolytic Anemia Due to Immunoglobulin G Autoantibody Exacerbated by Epstein-Barr Virus

Abstract: Most cases of autoimmune hemolytic anemia (AIHA) are caused by the production of an autoantibody that targets determinants on red blood cells (RBCs). This autoantibody can be immunoglobulin (Ig) G, IgM, or IgA. Some autoantibodies react optimally at 0° to 4°C (ie, cold agglutinin) and usually are clinically insignificant. High-titer cold agglutinins are associated with IgM autoantibody and complement fixation induced by infectious agents, including the Epstein-Barr virus (EBV). This case report describes a 31-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 16 publications
1
10
1
Order By: Relevance
“…Another case-control study observed a high prevalence of EBV-associated gastric carcinoma in patients with pernicious anemia [ 95 ]. Fadeyi et al (2015) [ 96 ] reported a case of fatal autoimmune hemolytic anemia (AIHA) associated with the reactivation of latent EBV infection in a 31-year-old man. The authors suggested that EBV infection triggered severe hemolysis, which aggravated the AIHA.…”
Section: CMV and Ebv Infection Impact In Patients With Hematologicmentioning
confidence: 99%
“…Another case-control study observed a high prevalence of EBV-associated gastric carcinoma in patients with pernicious anemia [ 95 ]. Fadeyi et al (2015) [ 96 ] reported a case of fatal autoimmune hemolytic anemia (AIHA) associated with the reactivation of latent EBV infection in a 31-year-old man. The authors suggested that EBV infection triggered severe hemolysis, which aggravated the AIHA.…”
Section: CMV and Ebv Infection Impact In Patients With Hematologicmentioning
confidence: 99%
“…Known hematopoietic symptoms of cGVHD include autoantibody production associated with AIHA and immune thrombocytopenic purpura . As reported by Fadeyi and colleagues, EBV induced broad warm‐reactive antibodies that exacerbated AIHA. On the other hand, it has also been reported that T‐cell depletion is associated with post‐HSCT AIHA .…”
Section: Discussionmentioning
confidence: 84%
“…Our patient had positive warm antibodies, which is unique. An extensive literature review showed only one single report of fatal AIHA due to IgG warm agglutination induced by EBV infection [ 6 ]. We believe that AIHA in our patient is likely due to reactivation of latent EBV infection.…”
Section: Discussionmentioning
confidence: 99%